(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The research paper attempts to explore the dialectics between consciousness and illusion in John Keats’s poem The Eve of St. Agnes. The contradiction between the conscious state and dream in the poem shows the incongruency and ambiguity that gives a fine vein of Romantic irony in the poem. It is a stance of isolated skepticism carried by an author towards his or her work, typically manifesting in literary self-consciousness and self reflection. The symmetrical paradox between two different realms of human life in the poem exposes the inherent contradictions provoked the interplay between reality and dream. To reveal the relationship and hostility between the ideal and the real empathically focusing into the contradictory existence of ultimate human reality is a key to Romantic irony. Madeline’s spirit to celebrate her chastity on the eve of St. Agnes enables her to celebrate consciousness as the bliss of ritual. The paper revolves around the unearthing of the inherent contradiction in the poem in reference to the theoretical illumination of Romantic irony using the critical perspectives of Schlegel, Colebrook and Mellor.